IC₅₀- Based Comparison of Astaxanthin and Tocotrienols Across Raw 264.7, A549, and Calu-3 Cells - Rusmidi, Muhamad Helmi Husaini; Mohamad Aini, Maliya Azilah; Iran, Nabiha; Ismail, Asmida; Pardi, Faezah; Wan Abdul Razak, Wan Razarinah; Abd Hafid, Sitti Rahma; Radzun, Khairul Adzfa (Journal of Science and Technology, 2026)
One of the most significant mediators of inflammation within immune and epithelial cells is nitric oxide (NO). It could be noted that NO production in excess may contribute to oxidative stress and tissue injury, thus, the measurement of this NO was considered as a beneficial endpoint in the search of nutraceutical compounds that possess anti-inflammatory effects. In the current work, the potential of astaxanthin and tocotrienols in inhibiting NO production across three cells, namely murine macrophages (RAW 264.7) and human lung epithelial cells (A549 and CALU-3) were compared. These cells were first induced with lipopolysaccharide (LPS, RAW 264.7) or interleukin-1β (IL-1β, A549 and CALU-3) and treated with increasing concentrations of astaxanthin or tocotrienols (1–25 µg/mL) for 24, 48, and 72 hours. For each time points, NO levels were measured by using the Griess assay while half-maximal inhibitory concentrations (IC₅₀) were derived from dose–response curves. The present work found that both natural compounds were able to inhibit the production of NO in a concentration-dependent manner among all studied cell lines. IC₅₀ values ranged from 4.97 ± 0.29 to 9.85 ± 1.28 µg/mL for astaxanthin and 6.97 ± 1.57 to 13.50 ± 1.58 µg/mL for tocotrienols across all three cell lines and time points. Astaxanthin was more likely to exhibit lower IC₅₀ values than tocotrienols in the studied cells. Nevertheless, statistically significant differences were only found in RAW 264.7 cells at 48 h and in CALU-3 cells at 48 h and 72 h, but not in A549 cells at any of the tested time points. The relatively narrow IC₅₀ range across time points further supports the reproducibility of the inhibitory responses of both compounds. To sum up, both studied compounds exhibited a comparable inhibitory activity against NO production. The results give a reliable comparative reference of the anti-inflammatory property of both compounds and can be a starting point of future mechanistic and in vivo research.